Aligning Project Portfolio Management and Corporate Strategy: An Exploration - TAHERI, FERESHTEH BAHMAN (2017)
The persistence of this dissertation is to explore the challenges encountered with alignment of project portfolio management to corporate level strategy of a private sector business in construction industry; nevertheless, this does not contradict the likelihood of generalizing the outcomes of this paper to other comparable industries. This dissertation further considers success factors influencing the management of project portfolios along with achieving higher level of corporate strategy and competitive advantage. The research findings are based on the inductive qualitative case approach with regard to management of a construction development in UAE who fails to achieve the alignment of corporate strategy with the project portfolio. These findings ascertain the effectiveness of project portfolio management and aligning it with the corporate strategy of the organization and further confirms that lack of each factor may have negative consequence on the success of the project portfolio and hence the organization development. The review of literature suggests that management of project portfolios in a private construction division seeks existence and implementation of some success factors affecting the project portfolio. These factors consist of: effective selection and prioritization of projects, balancing of priorities, resource allocation, flexibility in allocating resources to maintain the balance, termination of unnecessary offered projects and unsuitable resources, effective planning and control, handling conflicts and pressures, linking the projects with portfolio’s objectives, and alignment of the strategy with project portfolio goals. On the other hand, it also determines the success factors influencing implementation of corporate strategy that include: coordination, control, and competitive advantage through businesses, and organization. Success level of the alignment of project portfolio with corporate strategy depends on implementation of these factors and how well these factors are progressed. The study values the challenges of project portfolio management in construction development and targets the managerial positions and leading teams as well as decision makers to reconsider their actions towards better management and success of the business.